PENGARUH SELF EFFICACY TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI SMPN 2 TEMBILAHAN HULU - Nadia Eka Putri; Sri Kartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims is to determine the effect of self efficacy on student learning achievements in social studies subject at the grade VIII SMPN 2 Tembilahan Hulu. The population of this research is all of grade VIII students in SMPN 2 Tembilahan Hulu totaling 140 students. Data collection techniques used in this study are questionnaires and documentary in the form of report cards. The data analysis technique used in this study is simple linear regression with the help of the SPSS version 22 program which was previously tested for classic assumptions, namely normality test, heteroscedasticity test and t-test. The results showed that there was a significant effect between self efficacy on student learning achievement and R Square value of 28%. Self efficacy has a positive effect on student learning achievements, meaning that self-efficacy of students can improve student learning achievements. Thus to improve student learning achievement high self efficacy is needed so that the learning process is more effective.Key Words: Self efficacy, Learning Achievements.